Culture & identity : life stories for counselors and therapists - Thomas, Anita Jones (SAGE, 2011)
Culture and Identity: Life Stories for Counselors and Therapists, Second Edition combines rich and powerful real life autobiographies with sound theoretical formulations that explore race, ethnicity, gender, class, religion, as well as, in this edition, sexual orientation and disability.